2021
DOI: 10.3390/ijms22084139
|View full text |Cite
|
Sign up to set email alerts
|

YABBY Genes in the Development and Evolution of Land Plants

Abstract: Mounting evidence from genomic and transcriptomic studies suggests that most genetic networks regulating the morphogenesis of land plant sporophytes were co-opted and modified from those already present in streptophyte algae and gametophytes of bryophytes sensu lato. However, thus far, no candidate genes have been identified that could be responsible for “planation”, a conversion from a three-dimensional to a two-dimensional growth pattern. According to the telome theory, “planation” was required for the genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 125 publications
(351 reference statements)
1
26
0
Order By: Relevance
“…The YABBY gene family contains several transcription factor members present in all seed plants [1,2]. The family members have important functions in plant growth and development, such as the polarity establishment in lateral organs, the formation and development of leaves and flowers, and the response to internal plant hormone and external environmental stress signals [3,4]. The family was initially named after the Australian freshwater crayfish following the discovery of the first member, CRABS CLAW, of which the mutation (crc-1) can result in apically unfused carpels in Arabidopsis thaliana [5].…”
Section: Introductionmentioning
confidence: 99%
“…The YABBY gene family contains several transcription factor members present in all seed plants [1,2]. The family members have important functions in plant growth and development, such as the polarity establishment in lateral organs, the formation and development of leaves and flowers, and the response to internal plant hormone and external environmental stress signals [3,4]. The family was initially named after the Australian freshwater crayfish following the discovery of the first member, CRABS CLAW, of which the mutation (crc-1) can result in apically unfused carpels in Arabidopsis thaliana [5].…”
Section: Introductionmentioning
confidence: 99%
“…Determination of cell fate and specification of cell layers in SAMs as well as in leaves during their development requires precise regulation of symplastic exchange between cells. A whole orchestra of regulators, such as transcription factors, RNA, and small molecules like hormones move through PD enabling SAM functioning as well as proper development of leaves from leaf primordia (Kitagawa and Jackson, 2017 ; Liu and Chen, 2018 ; Bhatia et al, 2021 ; Maksimova et al, 2021 ; Romanova et al, 2021 ). Moreover, also in the mature leaves, exchange of regulatory molecules as well as assimilates between cells and tissues via PD is a highly important and finely tuned process (Cui et al, 2014 ; Liu and Chen, 2018 ; Dmitrieva et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on evolutionary relationships, the angiosperm YABBY genes can be classified into five subfamilies—YAB1, CRC, INO, YAB2, and YAB5 [ 10 , 11 ]. Substantial evidence has demonstrated that the YABBY genes play important roles in many aspects of plant growth and development, such as lateral organ development, establishment of polarity, and reproductive organ development in angiosperms [ 12 , 13 ]. In Arabidopsis, four genes— FIL , YAB2 , YAB3 , and YAB5 —are involved in vegetative tissues development [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence has demonstrated that the YABBY genes play important roles in many aspects of plant growth and development, such as lateral organ development, establishment of polarity, and reproductive organ development in angiosperms [ 12 , 13 ]. In Arabidopsis, four genes— FIL , YAB2 , YAB3 , and YAB5 —are involved in vegetative tissues development [ 13 , 14 , 15 ]. FIL , YAB2 , and YAB3 are specifically expressed in all lateral organ primordia derived from the apical and flower meristems [ 2 , 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%